Molecular Mechanisms of Steroid Hormone Biosynthesis and Action - Tremblay, Jacques J. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Steroids are essential hormones that regulate biological processes across their lifespan. Steroid hormone production and action must be tightly controlled otherwise there can be detrimental effects on physiological function leading to disease. This reprint contains original and review articles by experts at the cutting edge of their fields published in a Special Issue on the "Molecular mechanisms of steroid hormone biosynthesis and action" of the International Journal of Molecular Sciences. The topics include: 1) Steroid hormone biosynthesis, including substrate availability, mechanism of steroidogenic enzyme action, and the impact of mutations; 2) Molecular and cellular regulation of steroidogenesis, including steroidogenic cell response to hormone stimulation, signaling pathways, kinases, transcription factors, and gene expression; 3) Molecular mechanisms of endocrine disruptor action on steroidogenic cells; and 4) New tools and approaches to detect and study steroid hormones.